Analisis Kelimpahan Kepiting Bakau (Scylla sp.) di Kawasan Hutan Mangrove Kecamatan Alas Barat Kabupaten Sumbawa - Muhammad Zulfiqri; Dwi Mardhia; Dedi Syafikri; Syamsul Bachri (Indonesian, 2020)
Coastal District of Alas Barat has mangrove forest resources that have been degraded to environmental pressures due to human activities that is the conversion of land into pond areas. Mangrove ecosystems is an important role for marine and coastal ecology, which is the habitat of mangrove crabs (Scylla sp). Mangrove crab is a high commercial value fishery commodity. This study aims to determine the abundance of mangrove crabs (Scylla sp) in the mangrove forest area of ??Alas Barat District. The method used in this research is descriptive method with survey techniques. The research area is divided into 3 stations. The mangrove crab found was a type of Scylla serrata and Scylla paramamosain. The highest abundance of mangrove crabs was found at Station 1 (Gontar Baru) at 54.55%, followed by Station 2 (Karang Padak) at 23.23% and the lowest at Station 3 (Labuh Mapin) at 22.22%. The highest abundance at Station 1 type Scylla serrata is 11.66 ind / 100m² and the lowest at station 3 is 1.66 ind / 100m² while for Scylla paramamosain type, the highest abundance is at station 1 at 6.33 ind / 100m² and the lowest at station 2 as much as 5 ind / 100m².